PEMANFAATAN PAPAN KOSA KATA PEMANTIK UNTUK PENGUATAN LITERASI BACA SISWA SDIT AL-MAHMUD - Qonita Aulia Haq; Wardatun Nazia; Indana Julfan; Erni Yulianti; Risma; Syafruddin Muhdar (STKIP Subang, 2026)
Reading literacy is a fundamental skill that should be developed from the elementary school level, as it serves as the foundation for students to understand information, acquire knowledge, and participate effectively in the learning process. However, many students still face difficulties in recognizing new vocabulary, understanding word meanings, and connecting information obtained from reading materials. This condition highlights the need for instructional media that can support literacy activities in an engaging manner and align with the characteristics of elementary school learners. This study aimed to describe the utilization of a trigger vocabulary board as an effort to strengthen the reading literacy of second-grade students at SDIT Al-Mahmud. The research employed a qualitative descriptive approach. The participants consisted of 20 second-grade students and one classroom teacher. Data were collected through observation, interviews, and documentation, and were analyzed using data reduction, data presentation, and conclusion drawing techniques. Data validity was ensured through source triangulation and technique triangulation. The findings revealed that the use of the trigger vocabulary board helped students recognize and understand new vocabulary more easily through activities such as reading, observing, pronouncing, and applying words in simple sentences. The media also encouraged students to participate more actively in classroom learning, increased their interest in reading, and enhanced their confidence in presenting their learning outcomes. In addition, the vocabulary board assisted teachers in creating a more interactive, engaging, and meaningful learning environment. Although several students still required more intensive guidance in reading activities, the overall implementation of the trigger vocabulary board contributed positively to the improvement of students’ reading literacy. Therefore, this media can be considered an effective alternative for supporting sustainable literacy programs in elementary schools.